Antistressor effect of Costus speciosus on noise induced immunological changes in rats - Saraswathi Ilango; Saikumar P; Sembulingam K; SaiKarthik Jayakumar (International journal of research in pharmaceutical sciences, 2020)
Costus speciosus is being widely used in Indian folk medicine for treating various disorders. Environmental noise pollution is supposed to be an important factor for many health problems and it causes immune abnormalities. In the present study immune-regulating potential of Costus speciosus extract was evaluated during acute and subacute noise stress conditions. Adult Wistar albino rats were exposed to acute noise stress and subacute noise stress and then the effect of ethanolic Costus speciosus rhizome extract on immunological parameters such as phagocytic index, avidity index, neutrophil adherence test and total leucocyte count were studied. Neutrophil adherence and total leukocyte counts were found decreased and the percentage of avidity and phagocytic index were significantly increased in the stressed group of rats. The result of statistical analysis showed that, the pre-treatment with Costus speciosus extract significantly altered favourably the levels of immunological parameters. Ethanolic extract of Costus speciosus rhizome have the potential to prevent noise stress induced changes in rodent immune system and has a strong immunomodulatory prospective applicable to clinical practices.